Accuracy of radiographer comment following a two-month experiential and blended learning in appendicular skeleton X-ray interpretation: The Singapore experience. Issue 1 (February 2021) - Del Gante, E.; Kumar, M.; McEntee, M.; Sng, L.H.; Tan, C.Y.Y.; Yeo, C.W.K.; Sim, W.Y.; Ekpo, E.
Abstract: Introduction: The value of combined blended and experiential learning on radiographer diagnostic comment has not been explored. This study aims to examine the accuracy of image interpretation comment of radiographers who received a period of blended and experiential learning in Radiographer Abnormality Detection Systems (RADS). Methods: We evaluated the diagnostic opinions of 13 radiographers who received a blended training and experiential learning (a process of self-learning and reflection) in RADS. Radiographers' opinions on 16, 483 images were examined using the final radiologists' report as a reference standard. For each radiographer, we recorded the number of true positive, true negative, false positive and false negative opinions and MedCal® was used to calculate diagnostic performance and error rates. A t-test was used to assess whether the number of images read was associated with performance and whether the radiographers retained performance over time. Results: Sensitivity ranged from 87.4 (84.0–90.2) to 98.9 (97.5–99.7) with a mean of 94.3 (93.6–94.8). Specificity varied from 96.4 (94.8–97.5) to 99.9 (99.41–100.0) with a mean of 98.2 (97.9–98.4). Diagnostic accuracy ranged from 93.1 (91.5–94.4) to 99.5 (98.9–99.8) with a mean of 96.9 (96.6–97.1). The mean false positive rate was 0.018 (range: 0.010–0.031) with a false negative rate of 0.057 (range: 0.026–0.11). There were no differences in performance between the first and latter nine months of providing opinions and the number of images reviewed was not associated with performance. Conclusion: Radiographers who received blended and experiential learning in RADS provide accurate diagnostic comments on plain emergency appendicular skeleton radiographs. Implication for practice: A combined blended and experiential learning can equip radiographers to provide diagnostic opinion on plain appendicular skeleton radiographs.